Beyond Carrot and Stick: the Effect of Conflict Resolution on Crime Control in China - Su, Zheng (The British journal of criminology, 2021)
The question of what works in crime control has been frequently discussed over the past few decades. However, knowledge about and evidence from China is limited. This paper evaluates the effectiveness of three strategies of crime control—the ‘stick policy’, the ‘carrot policy’ and conflict resolution—in China, using a provincial panel data from 1988 to 2014. The results suggest that (1) the ‘carrot policy’ with social welfare provision helps to prevent crime, while the ‘stick policy’ with increasing judicial expenditure does not have a significant effect; (2) conflict resolution functions as an effective strategy of crime control. The policy implication is that, to prevent crime and maintain social order in a transitional society like China, government might need to shift its policy orientation away from strengthening coercive power to focussing on improving people’s livelihood and facilitating conflict resolution.